COVID-19 and inequities in the Americas: lessons learned and implications for essential health services - Anselm J.M. Hennis; Anna Coates; Sandra del Pino; Massimo Ghidinelli; Rodolfo Gomez Ponce de Leon; Edwin Bolastig; Luis Castellanos; Renato Oliveira e Souza; Silvana Luciani (Pan American Health Organization, 2021)
The COVID-19 pandemic has exacerbated social, economic, and health-related disparities, which disproportionately affect persons living in conditions of vulnerability. Such populations include ethnic groups who face discrimination and experience barriers to accessing comprehensive health care. The COVID-19 pandemic has exposed these health disparities, and disruptions of essential health services have further widened the gaps in access to health care. Noncommunicable diseases are more prevalent among groups most impacted by poor social determinants of health and have been associated with an increased likelihood of severe COVID-19 disease and higher mortality. Disruptions in the provision of essential health services for noncommunicable diseases, mental health, communicable diseases such as HIV, tuberculosis, and malaria, and maternal and child health services (including sexual and reproductive health), are projected to also increase poor health outcomes. Other challenges have been an increased frequency of interpersonal violence and food insecurity. Countries in the Americas have responded to the disruptions caused by the pandemic by means of health service delivery through telemedicine and other digital solutions and stepping up social service support interventions. As vaccinations for COVID-19 create the opportunity to overcome the pandemic, countries must strengthen primary health care and essential health services with a view to ensuring equity, if the region is to achieve universal health coverage in fulfillment of the Sustainable Development Goals.